Association between body fat percentage estimated by DXA and Jackson and Pollock equations in futsal players - Gomes, S. A.; Santos, T.; Silva, R. C.; Alves, M. A. R.; Soares, B. H.; De Sousa, L. L.; Leite, M. M.; Gomes, L. L.; Mota, M. R.; Ferreira, C. E. S. (Journal of Physical Education and Sport, 2022)
Futsal is a sport practiced by tens of millions of people around the world. Among its characteristics, the great variety of motor actions stands out, as well as the high intensity of effort, and the high demand that such a combination imposes on the body. Such dynamics demand rigorous monitoring of the athlete in several aspects, among which, is body composition. And since there are several equations to identify body composition by the percentage value of body fat that can be used in this population, there is no consensus on which is the most appropriate, and consequently, recommended for use. In view of the above, the manuscript aimed to analyze a possible association between body fat percentage (BF%) estimated with DXA and with three different body density (BD) equations for consequent estimation of %BF in male futsal athletes. To do so, the values obtained were submitted to analysis of variance, correlation, regression, and relative and absolute reliability. Although the BF% estimated with the three equations, seven skinfolds (7SF), three skinfolds 1 (3SF1) and three skinfolds 2 (3SF2), showed high or very high correlations with the value estimated with DXA, 7SF and 3SF2 led to overestimation of BF%, while the estimate with 3SF1 did not differ significantly from the value estimated with DXA. Furthermore, 3SF1 showed an absolute reliability that represents a difference of approximately half a percentage point compared to the estimate with DXA, an excellent relative reliability, and a coefficient of determination comparable to equations applied to the very profile of athletes for which they were developed. Thus, in the absence of a specific equation to estimate BD, and consequently %BF, in professional futsal athletes, the adoption of 3SF1 is recommended. It is also pertinent that future similar studies seek to reach a larger sample size, which enables the development of a specific equation for this public and seek to do the same with female professional futsal athletes.